Fabrication and evaluation of an oxygen microelectrode applicable to environmental engineering and science. Issue 3 (1st June 2002) - Lu, R; Yu, T
Abstract : This paper introduces the fabrication procedure and evaluation method of an oxygen microelectrode applicable to environmental engineering and science research. The theory and development of an oxygen microelectrode technique are introduced. The fabrication procedure of a combined oxygen microelectrode with small-tip diameter (1520 μμm) is described in detail. This microelectrode was then evaluated by subjecting it to a polarization voltage of 0.8 V and calibrating against known dissolved oxygen concentrations from zero to air saturation. The results of the evaluation demonstrated that the fabrication procedure reported in this paper was successful. This microelectrode had a fast response time (<2 s), stable reading with good calibration linearity ( R 2 = 1), low residual current signal (6 pA), and low stirring effect (4%). No electromagnetic interference was observed when this combined oxygen microelectrode was used under both laboratory and field conditions. The combined oxygen microelectrode fabricated using this procedure can be used for in situ measurement of dissolved oxygen in wastewater biofilms under field conditions. Key words : microelectrode, microsensor, oxygen, fabrication, polarization, calibration, biofilm, wastewater.